Application of Moodle as Authentic Assessment in Learning Mathematics in SMK - HE, Chrisnawati; Wulandari, Arum Nur; Sutopo, Sutopo; Kuswardi, Yemi (Universitas Sebelas Maret, 2020)
The purpose of this study was to develop an assessment system using Moodle e-learning to improve mathematics learning outcomes in terms of knowledge, skills and attitudes of students. The development design in this study is more on how to develop learning activities with authentic assessment that must be carried out by the teacher which of course will be very difficult if everything is paper-based. The implementation of a reliable assessment with easy administration by the teacher becomes the consideration of the researcher. And with regard to the pandemic conditions that are being experienced by the Indonesian nation, online learning is an option for students and teachers. Even in the assessment that must be carried out. For this reason, the Moodle application is an alternative that allows students to access teaching materials and practice problem solving easily. This is very interesting to do a development study in SMK, why? Because vocational students usually lack positive attitudes towards mathematics. The use of the Moodle application in learning mathematics in the classroom is certainly the teacher's job to limit the time to face students, and the lack of positive attitudes of these students into